Granulomatose com poliangiíte na infância: experiência de um centro de referência terciário no Ceará (BR) - Camila Emidio Bastos; Marco Felipe Castro da Silva; Carlos Nobre Rabelo Júnior (Sociedade Brasileira de Pediatria, 2023)
Granulomatosis with polyangiitis (GPA) is an ANCA-associated necrotizing granulomatous vasculitis. It is rare in the pediatric population and predominantly affects small and medium-sizes blood vessels; it preferentially involves the kidneys and the upper and lower respiratory tract. This retrospective case series looked into the medical charts of children and adolescents aged up to 18 years diagnosed with the condition based on the EULAR/PReS criteria in the period ranging from 2014 to 2019. It describes clinical characteristics, laboratory findings and treatment options, along with the progress of GPA in children. In our series, GPA predominantly affected females (80%) and the median age at diagnosis was 11.1 years. The classic clinical triad comprising granulomatous inflammation, pauci-immune necrotizing glomerulonephritis, and upper and lower respiratory tract involvement, was highly prevalent, and delays in diagnosis occurred particularly in individuals with mild kidney or lung involvement. Laboratory findings included elevated erythrocyte sedimentation rate, anemia, and hematuria; alterations included sinus disease, pulmonary infiltrates, nodules, and cavitation seen on CT scans of the head and chest, all of which are key diagnostic elements. All patients were treated with glucocorticoids and cyclophosphamide. Morbidity remained significant and unchanged throughout the course of the disease. Clinical and laboratory findings and prescribed treatments were consistent with the literature. Given its severity, this disease requires early recognition, aggressive initial treatment, and long-term patient follow-up.